Effect of concrete modification on shear of connections for timber–concrete composites. Issue 5 (24th October 2019) - Richard, Pierre; Liu, Zuowei; Descamps, Thierry; Sikora, Karol S.
Abstract : Timber–concrete composites (TCCs) take advantage of the properties of timber and concrete simultaneously. TCC slabs consist of timber beams or a timber deck, which resist tensile and bending stresses, connected through different types of shear connectors to an upper concrete slab, which withstands compressive stresses. The stiffness and strength of the slab are mostly defined by the properties of the connectors. To avoid the use of external materials that could be environmentally harmful, micro-notch connections were tested. These micro-notch connections are notches cut into timber elements and filled with wet concrete. The research focused on the influence of the gap between the micro-notches, the experimental configuration, the concrete composition and the concrete curing process on the shear strength of the connectors. The concrete compositions included ground granulated blast-furnace slag (GGBS) and superabsorbent polymer (SAP). These additives were used to evaluate their compliance with the shear strength of the TCC connections. GGBS was used to reduce the cement content in the concrete mix and SAP was used as a water-entraining agent to reduce the autogenous shrinkage of the concrete.